Effective transverse elastic properties of unidirectional fiber reinforced composites. (November 2016) - Beicha, D.; Kanit, T.; Brunet, Y.; Imad, A.; Moumen, A. El; Khelfaoui, Y.
Highlights: Random versus periodic microstructures for elasticity of fiber reinforced composites. Investigation on the elastic response of hexagonal and random morphology. Stresses were always higher for random distribution than for periodic one. The effective properties strongly depend on the composite microstructure. Microstructures haven't significant influence on effective properties at low volume fractions. Abstract: The purpose of this work was to study the influence of microstructure on effective transverse elastic behavior of fiber reinforced composites. Two microstructures were taken into account, hexagonal periodic and random arrangements of fibers. Unlike classical results at low fiber volume fractions and low Young's modulus contrast between fibers and matrices, results provided by finite elements simulations have shown that microstructure strongly affect the effective properties of composite for both high volume fractions and Young's modulus contrast. Results were compared to most common analytical models for composites elasticity.